Development and optimisation of a multi-component workplace intervention to increase cycling for the Cycle Nation Project - Connell, Hayley; Logan, Greig; Somers, Camilla; Baker, Graham; Broadfield, Sarah; Bunn, Christopher; Harper, Luke D.; Kelly, Paul; McIntosh, Emma; Pell, Jill P.; Puttnam, Jill; Robson, Sam; et al. (Frontiers in Sports and Active Living, 2022)
The Cycle Nation Project (CNP) aimed to develop, test the feasibility of and optimize a multi-component individual-/social-level workplace-based intervention to increase cycling among office staff at a multinational bank (HSBC UK). To do this, we first explored barriers to cycling in a nationally-representative survey of UK adults, then undertook focus groups with bank employees to understand any context-specific barriers and ways in which these might be overcome. These activities led to identification of 10 individual-level, two social-level, and five organizational-level modifiable factors, which were mapped to candidate intervention components previously identified in a scoping review of cycling initiatives. Interviews with HSBC UK managers then explored the practicality of implementing the candidate intervention components in bank offices. The resultant pilot CNP intervention included 32 core components across six intervention functions (education, persuasion, incentivisation, training, environmental restructuring, enablement). Participants received a loan bike for 12-weeks (or their own bike serviced), and a 9-week cycle training course (condensed to 6 weeks for those already confident in basic cycling skills), including interactive information sharing activities, behavior change techniques (e.g., weekly goal setting), bike maintenance training, practical off-road cycling skill games and on-road group rides. Sessions were delivered by trained bank staff members who were experienced cyclists. The CNP pilot intervention was delivered across three sites with 68 participants. It was completed in two sites (the third site was stopped due to COVID-19) and was feasible and acceptable to both women and men and across different ethnicities. In addition, the CNP intervention was successful (at least in the short term) in increasing cycling by 3 rides/week on average, and improving perceptions of safety, vitality, confidence, and motivation to cycle. Following minor modifications, the long-term effectiveness and cost-effectiveness of the CNP intervention should be tested in a full-scale randomized controlled trial.